Improved dissolution and bioavailability of silymarin delivered by a solid dispersion prepared using supercritical fluids - Gang Yang; Yaping Zhao; Nianping Feng; Yongtai Zhang; Ying Liu; Beilei Dang (Elsevier, 2015)
The objective of this study was to improve the dissolution and bioavailability of silymarin (SM). Solid dispersions (SDs) were prepared using solution-enhanced dispersion by supercritical fluids (SEDS) and evaluated in vitro and in vivo, compared with pure SM powder. The particle sizes, stability, and contents of residual solvent of the prepared SM-SDs with SEDS and solvent evaporation (SE) were investigated. Four polymer matrix materials were evaluated for the preparation of SM-SD-SEDS, and the hydrophilic polymer, polyvinyl pyrrolidone K17, was selected with a ratio of 1:5 between SM and the polymer. Physicochemical analyses using X-ray diffraction and differential scanning calorimetry indicated that SM was dispersed in SD in an amorphous state. The optimized SM-SD-SEDS showed no loss of SM after storage for 6 months and negligible residual solvent (ethanol) was detected using gas chromatography. In vitro drug release was increased from the SM-SD-SEDS, as compared with pure SM powder or SM-SD-SE. In vivo, the area under the rat plasma SM concentration-time curve and the maximum plasma SM concentration were 2.4-fold and 1.9-fold higher, respectively, after oral administration of SM-SD-SEDS as compared with an aqueous SM suspension. These results illustrated the potential of using SEDS to prepare SM-SD, further improving the biopharmaceutical properties of this compound.